Adsorpsi Biocharcoal Kulit Durian (Durio zibethinus Murr) Terhadap Ion Kadmium - Kusuma, I Gede Yoga Nata; Napitupulu, Mery; Walanda, Daud K. (Universitas Tadulako, 2015)
Research on the adsorption biocharcoal of durian (durio zibethinus murr) bark to cadmium ion has been conducted. Heavy metal ions are toxic and generally as a major pollutant to the environment. Handling of waste containing heavy metal ions, especially Cd2+ ions have been carried out and need to be developed. This study described the ability of biocharcoal (biological charcoal) of durian bark to adsorb Cd2+ ions from their solutions. The method in this study was a laboratory experiment using biological charcoal powder of durian bark as an adsorbent of Cd2+ ions. Concentration of Cd2+ ions absorbed was measured using atomic absorption spectrophotometer (AAS) at a wavelength of 228.8 nm. The results showed the optimum Cd2+ ion absorbed was at 80 mg biocharcoal with the percentage of the Cd2+ ion absorbed up to 93.46%, where the weight of the Cd2+ ion absorbed was 16.62 mg/g. The optimum pH was at 7.0 with the percentage of the Cd2+ ion absorbed up to 97.94%, where the weight of the Cd2+ ion absorbed was 17.42 mg/g. The optimum concentration was at 20 ppm with the percentage of the Cd2+ ion absorbed up to 91.97%, where the weight of Cd2+ ion absorbed was 11.42 mg/g. The maximum absorption capacity of biocharcoal to the Cd2+ ion using the Langmuir isotherm adsorption equation was 33.33 mg/g of biocharcoal.